(untitled) (El-Wahat Journal for Research and Studies, 2016)
A filamentous actinobacterial strain, Planomonospora sp. PM18, was isolated from a Saharan soil sample collected in Béni-Abbès (Béchar). Antimicrobial activity of this strain was evaluated on ISP 2, Bennett and Hickey–Tresner Agar (HTA) media against different test pathogens. It showed a strong activity against the Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA), on ISP 2, Bennett and Hickey–Tresner agar media. Key words: Planomonospora, Actinobacteria, Saharan soil, methicillin-resistant Staphylococcus aureus, Antagonistic potential.